Strengthening Internal Responsibilities of Good Parenting Skill in Process of Child Protection from Dangers of Drug Abuse: An Phenomenology Social Life in North Kalimantan - Adri Patton (Budapest International Research and Critics University, 2021)
The family is a household that is related by blood or marriage or provides the implementation of basic instrumental functions and expressive functions of the family for its members who are in a network. For this reason, the research wants to know the Strengthening of the Functions and Responsibilities of Parents, Families and Society in the Process of Parenting and Protection of Children from the dangers of drugs in North Kalimantan Province (Good Parenting Skill). The theory used in this research is Grand Theory (Umbrella Theory); it is any attempted theory of the overall explanation of social life, history, or human experience. Broadly speaking, trying to explain a problem or case. Middle-range theory as a theory that lies between minors but requires hypotheses that develop in abundance. Applied Theory, namely the Theory of Child Protection. The research method used is normative social studies research or has similarities with doctrinal research (doctrinal research). The data collection technique used is library research or document study. The results of this study, namely they cannot effectively control children's behavior in terms of keeping children away from the dangers of drugs in the province of North Sumatra. So that parents are indifferent or not interested and pay less attention to the behavior of their children so that they are permissive.